A foreign faith in a Christian Domain: the Historical Development of Islam among the Igbos of Southeastern Nigeria - Saheed Ahmad Rufai, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2012)
Igboland, which is geographically located in the Southeastern part of Nigeria, was the last part of the country to witness the advent of Islam. This was owing to the fact that the people are predominantly Christian and adherents of African traditional religions. Notwithstanding, Islam spread to the region in the 19th century and has since been earning itself new adherents among the local people. However, there has not been a systematic study of the spread, growth and development so far of the religion among the Igbo people whose adherents are a minority and to whom the religion is alien. The purpose of this article is to trace the historical development of the religion in the region by identifying the factors instrumental to its spread as well as the initiatives of the early Muslims. The significance of such a historical analysis lies in its potential to provide some new insight into how a minority survives with their religions persuasion in the face of majority adherents of dominant faiths. The article employs a combination of the historical and the analytical methods and concludes that with appropriate da’wah machineries in place, Islam stands a good chance of becoming the religion of the majority of the Igbo people.